2015
DOI: 10.1002/hbm.23015
|View full text |Cite
|
Sign up to set email alerts
|

Motor imagery of hand actions: Decoding the content of motor imagery from brain activity in frontal and parietal motor areas

Abstract: How motor maps are organized while imagining actions is an intensely debated issue. It is particularly unclear whether motor imagery relies on action‐specific representations in premotor and posterior parietal cortices. This study tackled this issue by attempting to decode the content of motor imagery from spatial patterns of Blood Oxygen Level Dependent (BOLD) signals recorded in the frontoparietal motor imagery network. During fMRI‐scanning, 20 right‐handed volunteers worked on three experimental conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(66 citation statements)
references
References 81 publications
(116 reference statements)
3
62
0
1
Order By: Relevance
“…Previous virtual lesion studies of the right parietal lobe demonstrated degraded accuracy of MI (Fleming, Stinear, & Byblow, ). In a recent study, the activation pattern within the parietal lobe (but also the premotor cortex) was associated with imagined action content (Pilgramm et al, )—again increase in demand to remember the movement pattern increases recruitment within processing resources.…”
Section: Discussionmentioning
confidence: 95%
“…Previous virtual lesion studies of the right parietal lobe demonstrated degraded accuracy of MI (Fleming, Stinear, & Byblow, ). In a recent study, the activation pattern within the parietal lobe (but also the premotor cortex) was associated with imagined action content (Pilgramm et al, )—again increase in demand to remember the movement pattern increases recruitment within processing resources.…”
Section: Discussionmentioning
confidence: 95%
“…The noise level of visual stimulus representations in retinotopic cortex is affected by the (in)congruency of co-occurring sounds (de Haas et al 2013b). Category-specific sounds and visual imagery can be decoded from early visual cortex, even with eyes closed , and the same is true for imagined hand actions (Pilgramm et al 2016). At the same time, the location of visual stimuli can bias the perceived origin of sounds (Thomas 1941), and a visible face articulating a syllable can bias the perception of a concurrently presented (different) syllable (McGurk & MacDonald 1976).…”
Section: Andy Clarkmentioning
confidence: 93%
“…An interesting next step could now involve a more in-depth examination using multi-voxel pattern analysis (MVPA) of fMRI data into the precise anatomical substrates involved for different AO+MI states. Pilgramm et al (2016) recently used MVPA to discriminate between different types of imagined actions purely on the basis of brain activity recorded in frontal and parietal areas, while Zabicki et al (2016) distinguished between different action types within two modalities (imagined and executed). Furthermore, Filimon et al (2015) also decoded the neural signatures for independent AO, MI and execution of a reaching action within brain areas jointly activated by all three modalities.…”
Section: Conceptualizing Concurrent Action Observation and Motor Imagmentioning
confidence: 99%